Analysis of the Implementation Islamic Business Ethics Principles in Transactions on Facebook - Anis Nala Falikhah; Sabrina Rosa Dewi; Drajat Setiawan; Hendri Hermawan Adinugraha (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
In the digital era, the importance of implementing Islamic business ethics principles in online buying and selling transactions is increasingly prominent. This research explores the implementation of Islamic Business Ethics in online transactions in Indonesia through the Facebook platform. Faced with the rapid development of online businesses, the study aims to analyze the extent to which the principles of Islamic Business Ethics have been applied in this environment. A qualitative descriptive method was employed, involving in-depth interviews with traders and buyers, as well as observations of online business practices. The research findings reveal that buying and selling transactions through Facebook in Indonesia have not fully adhered to the principles of Islamic Business Ethics optimally. Despite some sellers incorporating the balance principle by providing detailed explanations of products and setting appropriate prices, there remains a discrepancy between the representation of products and the reality experienced by buyers. Deceptive practices, such as using inaccurate product images to enhance attractiveness, indicate that the principles of unity (tauhid) and benevolence (ihsan) are inadequately applied. Responses to buyer complaints also reflect a lack of individual seller responsibility. Therefore, this research recommends expanding efforts to strengthen integrity and transparency in online business practices to align with the principles of Islamic Business Ethics, creating a more ethical and trustworthy business environment in Indonesia.